The effect of growth conditions on the surface properties of Listeria monocytogenes - Nwaiwu, Ogueri (2011)
Due to the recent persistence of Listeria monocytogenes in food factory environments and an increase in outbreaks of Listeriosis, in particular some associated with duck meat products, an investigation was carried out to establish the potential effects of different growth conditions on the hydrophobicity of L. monocytogenes cells and to determine the behaviour of the cells in a minimal nutrient environment. It was found that duck meat extracts increased growth rate but did not alter the surface charge of the cells and when grown in minimal 010 and MCDB202 media the cells flocculated and showed more hydrophobicity than when grown in the rich media BHI. The modified surface of the organism behaved like an emulsifier and this led to the discovery for the first time, that there was formation of capsular exopolymeric substances (EPS) on the surface of planktonic cells of L. monocytogenes. After confirmation of the capsular EPS by two capsule stains, namely Nigrosin and Giemsa, the EPS was purified and proved to play a role in holding the cells together. It was also found to absorb water rapidly and can retain water for long periods suggesting that the EPS can contribute to the desiccation tolerance of L. monocytogenes cells embedded in a biofilm matrix. Chemical characterization of the EPS showed high levels of glycerol and phosphate indicating that the EPS is amphiphatic and may contain mainly glycerolphosphates.